2016
DOI: 10.1016/j.progpolymsci.2016.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Polymerizations with elemental sulfur: A novel route to high sulfur content polymers for sustainability, energy and defense

Abstract: Recent developments in the polymerizations of elemental sulfur (S 8 ) to prepare high sulfur content polymers are reviewed. While the homopolymerization of S 8 via ring-opening processes to prepare high molar mass polymeric sulfur has long been known, this form of polymeric sulfur is chemically unstable and depolymerizes back to S 8 . In the current report, we discuss the background into the production of sulfur via petroleum refining and the challenges associated with utilizing S 8 as a chemical reagent for m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
261
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 363 publications
(263 citation statements)
references
References 387 publications
(344 reference statements)
0
261
0
2
Order By: Relevance
“…An exception is the spontaneous ring-opening of arsenomethane,( MeAs) 5 (16), which produces an insoluble purple solid with semiconducting properties.E xperimental and theoretical studies attributed the low solubility to ab ackbone structure consisting of aladder of two stacked poly(methylarsine) linear chains (19,Scheme 3,top). [27] In as eminal work, [28] they described af acile method for preparing copolymers 24 with 1,3-diisopropenylbenzene (DIB), also termed CHIPS (chalcogenide hybrid inorganic/ organic polymers), achieving up to 90 wt %ofScontent. [25] Ther esulting soluble polymers have ap erfectly alternating sequence with [ER À CR 1 = CH] n repeat units (20,E= P, As or Sb;R= Ph or Me,R 1 = aryl or alkyl, Scheme 3, bottom) and preferentially adopt trans conformations.T he P-phenyl analogues are typically prepared by anionic ROP of phosphirenes (21,R 2 = Me) and obtained in somewhat higher yields.…”
Section: Catenation Of Main-group Elementsmentioning
confidence: 99%
“…An exception is the spontaneous ring-opening of arsenomethane,( MeAs) 5 (16), which produces an insoluble purple solid with semiconducting properties.E xperimental and theoretical studies attributed the low solubility to ab ackbone structure consisting of aladder of two stacked poly(methylarsine) linear chains (19,Scheme 3,top). [27] In as eminal work, [28] they described af acile method for preparing copolymers 24 with 1,3-diisopropenylbenzene (DIB), also termed CHIPS (chalcogenide hybrid inorganic/ organic polymers), achieving up to 90 wt %ofScontent. [25] Ther esulting soluble polymers have ap erfectly alternating sequence with [ER À CR 1 = CH] n repeat units (20,E= P, As or Sb;R= Ph or Me,R 1 = aryl or alkyl, Scheme 3, bottom) and preferentially adopt trans conformations.T he P-phenyl analogues are typically prepared by anionic ROP of phosphirenes (21,R 2 = Me) and obtained in somewhat higher yields.…”
Section: Catenation Of Main-group Elementsmentioning
confidence: 99%
“…Thes ynthesis of the NBD2 monomer was prepared according to literature procedures [14] and was then subjected to inverse vulcanization [15][16][17][18] with liquid sulfur (T = 130-160 8 8C) to afford poly(sulfur-random-NBD2)(poly(S-r-NBD2)), at two different feed ratios (70-wt %S /30-wt % NBD2 &5 0-wt %S /50-wt %N BD2). Copolymerization of these comonomers afforded amorphous,yellow,g lassy crosslinked networks.Structural characterization of these thermosets was done using 13 CC P-MAS solid-state NMR spectroscopy (Figure 3b), which confirmed that the norbornyl skeletal framework remained intact after polymerization, as indicated by the upfield resonances at 44 and 48 ppm from methylene and methine protons from NBD2.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…[13,19] In this process,s ulfur served as the backbone material, and aromatic carbon comonomers were bound to sulfur chains to form stable polymer complexes.T he inverse vulcanization method takes advantage of sulfursr ing-opening and chain-forming tendencies at elevated temperatures by binding divinyl molecules to the sulfur radicals that form when sulfursS 8 rings open ( Figure 3). [13,19] In this process,s ulfur served as the backbone material, and aromatic carbon comonomers were bound to sulfur chains to form stable polymer complexes.T he inverse vulcanization method takes advantage of sulfursr ing-opening and chain-forming tendencies at elevated temperatures by binding divinyl molecules to the sulfur radicals that form when sulfursS 8 rings open ( Figure 3).…”
Section: Inverse Vulcanizationmentioning
confidence: 99%